PENGARUH DEBIT ALIRAN AIR TERHADAP EFEKTIFITAS RADIATOR PADA MOTOR BAKAR BENSIN 4 LANGKAH DENGAN KAPASITAS SILINDER 1329 CC - Enzo W. B. Siahaan (Universitas Quality, 2018)
This research was conducted to determine the effect of water flow discharge on the effectiveness of radiators on Daihatsu Xenia Type 1.3 cars. Cooling is a support system for a machine that works and operates. The existence of a cooling system will be felt especially in large-capacity engine engines. And it can be concluded that this analysis only examines the effect of water flow discharge on the effectiveness of the radiator. The problem found in this analysis is the effect of water flow discharge on the effectiveness of the radiator. The purpose of this analysis is to examine the effect of water flow discharge on the effectiveness of radiators. The object of this analysis is a set of radiator tester devices consisting of several components and integrated measuring instruments. This tool is used for data retrieval using the Daihatsu Xenia Type 1.3 16 Valve engine. The analysis design used is experiments, by manipulating a variable to see the effect of the action. The independent variables are the flow rate of water (0.011, 0.016, 0.024, 0.028, 0.033 m3 / min) based on the engine speed (1500, 2000, 2500, 3000, 3500 rpm). The dependent variable is the effectiveness of the radiator. Each study took data three times. Retrieval of data analysis in the first minute shows that the higher water discharge makes the value of radiator effectiveness increase (at a discharge of 0.028 m3 / minute, 2500 rpm) so that in other words the water flow discharge affects the value of radiator effectiveness.